2021
DOI: 10.1073/pnas.1811725118
|View full text |Cite
|
Sign up to set email alerts
|

Nanoanalytical analysis of bisphosphonate-driven alterations of microcalcifications using a 3D hydrogel system and in vivo mouse model

Abstract: Vascular calcification predicts atherosclerotic plaque rupture and cardiovascular events. Retrospective studies of women taking bisphosphonates (BiPs), a proposed therapy for vascular calcification, showed that BiPs paradoxically increased morbidity in patients with prior acute cardiovascular events but decreased mortality in event-free patients. Calcifying extracellular vesicles (EVs), released by cells within atherosclerotic plaques, aggregate and nucleate calcification. We hypothesized that BiPs block EV ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 60 publications
0
13
0
1
Order By: Relevance
“…However, our data suggest that timing of BiP intervention in relation to ongoing atherosclerotic remodeling could influence mineral morphology and thus plaque stability. Previous studies using electron microscopy revealed that timing of BiP regimen affects the morphology and topography of plaque microcalcifications (less than 5 μm 2 ) [1]; starting BiP treatment in early plaque remodeling led to bigger individual mineral aggregates with higher surface roughness, while starting at later time points reduced both mineral aggregates size and surface roughness [1]. Furthermore, mineral aggregates associated with later BiP treatment beginning showed qualitatively disorganized and loose morphologies [1].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, our data suggest that timing of BiP intervention in relation to ongoing atherosclerotic remodeling could influence mineral morphology and thus plaque stability. Previous studies using electron microscopy revealed that timing of BiP regimen affects the morphology and topography of plaque microcalcifications (less than 5 μm 2 ) [1]; starting BiP treatment in early plaque remodeling led to bigger individual mineral aggregates with higher surface roughness, while starting at later time points reduced both mineral aggregates size and surface roughness [1]. Furthermore, mineral aggregates associated with later BiP treatment beginning showed qualitatively disorganized and loose morphologies [1].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using electron microscopy revealed that timing of BiP regimen affects the morphology and topography of plaque microcalcifications (less than 5 μm 2 ) [1]; starting BiP treatment in early plaque remodeling led to bigger individual mineral aggregates with higher surface roughness, while starting at later time points reduced both mineral aggregates size and surface roughness [1]. Furthermore, mineral aggregates associated with later BiP treatment beginning showed qualitatively disorganized and loose morphologies [1]. Finite element-based predictions of these previous data suggested that the microcalcifications associated with all BiP treatment groups would reduce plaque stress compared to non-treated controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mentioned drawbacks can be resolved by TEM, which is incompatible with large samples (e.g., most of the blood vessels) due to a critically reduced amount of analysable tissue, needs difficult sample preparation, and the final sample represents a single tissue snapshot rather than serial sections evenly distributed along or across the specimen. Notably, the visualisation of calcified tissues is often performed by means of density-dependent scanning electron microscopy (SEM), which implies the superimposing of images acquired by secondary and backscattered electron detectors and further assigning them to the distinct colour channels (e.g., green and red), thereby permitting the coloured mapping of calcific nodules and distinguishing them from soft tissues (51)(52)(53). The main advantage of this technique is that it allows the simultaneous visualisation of both topography and density in a single image (51).…”
Section: Discussionmentioning
confidence: 99%